Ambiguitance: How Douyin's Inconsistent Affordances Shape Streamer-Audience Relationships in Chinese Showroom Live Streaming - Zhang, Lin; Wang, Yingwen (United States, 2026)
This study examines how Douyin's platform affordances enable regulatory-risky content and shape relationships between streamers and audiences in Chinese showroom live streaming—a controversial yet profitable genre characterized by intimate performances and virtual gifting. While existing research focuses on performers' labor and precarity, limited attention has been paid to how platforms enable content that operates at the edge of regulatory boundaries. Through a methodological triangulation combining walkthrough analysis, online observation, and in-depth interviews with female streamers, we introduce the concept of "ambiguitance": a constellation of contradictory affordances engineered across a platform's policy, algorithmic, and interface layers. Our findings reveal that while Douyin's policies explicitly restrict sexually suggestive content and discourage tipping, its traffic-driven algorithms implicitly incentivize edge-ball content, and its interface prioritizes monetization features over risk warnings. This ambiguitance creates a space where users navigate between explicit restrictions and implicit incentives, enabling the production and consumption of controversial content. Furthermore, it fosters hierarchical, competitive relationships characterized by uneven risk distribution, where streamers can leverage ambiguity for monetary gain but face disproportionate consequences when audiences weaponize platform policies through reporting. Streamers experience platform affordances as simultaneously empowering and restrictive. This research contributes a novel analytical framework for understanding how platforms strategically engineer governance gaps that serve their interests while displacing responsibilities onto users, offering implications for platform studies and digital labor research.
Selected Papers in Internet Research 2025. Research from the Annual Conference of the Association of Internet Researchers